Sardinian Landscape and Lighthouses - Satta, Alessio; Usai, Maria Pina; Puddu, Manuela (Ri-Vista. Research for landscape architecture, 2017)
Lighthouses are commonly perceived as extraordinary places on the edge between land and sea, with such a strong connection with the landscape to be considered as true landmarks. Remained for long time assigned to the exclusive use of the Italian Navy, most of lighthouses are now abandoned and vulnerable pieces of architectures, exposed to erosion, salt water and the unavoidable decay. This article analyses the Integrated Conservation Program (ICP) of public lighthouses developed by the public agency Conservatoria delle coste della Sardegna. The ICP is based on the Protocol of Integrated Coastal Zone Management and on the concept of conservation, intended as measures to preserve the historical heritage and enhance the architectures quality in relation with the Sardinian cultural landscape.